Risky sexual behaviour in context: qualitative results from an investigation into risk factors for seroconversion among gay men who test for HIV. Issue 6 (21st November 2008) - Elam, G; Macdonald, N; Hickson, F C I; Imrie, J; Power, R; McGarrigle, C A; Fenton, K A; Gilbart, V L; Ward, H; Evans, B G
Abstract : Objectives: The INSIGHT case-control study confirmed that HIV serodiscordant unprotected anal intercourse (SdUAI) remains the primary risk factor for HIV infection in gay men in England. This paper uses qualitative follow-up data to examine the contexts of SdUAI and other risk factors among the case-control study participants. Methods: In-depth interviews were conducted with 26 recent HIV seroconverters and 22 non-converters. Purposive selection was used to provide diversity in demographics and sexual behaviour and to facilitate exploration of risk factors identified in the case-control study. Results: Condoms were perceived as barriers to intimacy, trust and spontaneity. The potential consequences of the loss of these were traded off against the consequences of HIV infection. Previous negative HIV tests and the adoption of risk reduction strategies diminished the perceived threat of HIV infection, supporting beliefs that HIV was something that happened to others. Depression and low self-esteem, often combined with use of alcohol or other drugs, led to further risk taking and loss of control over risk reduction strategies. Conclusions: A range of psychosocial reasons led some men to engage in UAI with serodiscordant or unknown partners, despite high levels of risk awareness. Men in their mid-life, those in serodiscordant relationships and men that had experienced bereavement or other significant, negative, life events revealed factors related to these circumstances that contributed to increases in risky UAI. A diverse portfolio of interventions is required to build confidence and control over safer sex practices that are responsive to gay men's wider emotional needs.